2014
DOI: 10.1186/1471-2164-15-444
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the lipoxygenase (LOX) gene family in the Chinese white pear (Pyrus bretschneideri) and comparison with other members of the Rosaceae

Abstract: BackgroundLipoxygenases (LOXs), a type of non-haem iron-containing dioxygenase, are ubiquitous enzymes in plants and participate in the formation of fruit aroma which is a very important aspect of fruit quality. Amongst the various aroma volatiles, saturated and unsaturated alcohols and aldehydes provide the characteristic aroma of the fruit. These compounds are formed from unsaturated fatty acids through oxidation, pyrolysis and reduction steps. This biosynthetic pathway involves at least four enzymes, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 29 publications
(33 reference statements)
0
29
0
1
Order By: Relevance
“…Segmental gene duplication was also reported in the pear genome. Li et al [51] found a total of 70 collinear gene pairs in the pear genome, which might have resulted from wholegenome duplication in pear millions of years ago. Recently, Cao et al [52] observed high level of gene duplication in P. bretschneideri and reported that wholegenome and segmental duplication likely played key roles in expansion of the MYB gene family in pear.…”
Section: Evidence Of Ssr Duplicationmentioning
confidence: 99%
“…Segmental gene duplication was also reported in the pear genome. Li et al [51] found a total of 70 collinear gene pairs in the pear genome, which might have resulted from wholegenome duplication in pear millions of years ago. Recently, Cao et al [52] observed high level of gene duplication in P. bretschneideri and reported that wholegenome and segmental duplication likely played key roles in expansion of the MYB gene family in pear.…”
Section: Evidence Of Ssr Duplicationmentioning
confidence: 99%
“…Lipoxygenase, hydroperoxide lyase (HPL), and alcohol dehydrogenase (ADH) are key enzymes in the metabolism of aroma‐related esters in fruits (Both, Brackmann, & Thewes, ; Maschietto, Marocco, & Malachova, ; Tiggemann, Ballen, & Bocalon, ). Lipoxygenase can identify the 1,4‐isoprene structure of the unsaturated fatty acids, linoleic acid and linolenic acid, and oxidize the oxyhydroxy fatty acids to provide the substrate for subsequent synthesis of esters (Li et al, ). Hydroperoxide lyase is another important enzyme in the LOX pathway, which catalyzes the formation of hexanal from 13‐hydroperoxides (Ono, Handa, Koeduka, & Toyonaga, ).…”
Section: Resultsmentioning
confidence: 99%
“…It is a family of proteins that contain PLAT (Polycistin-1, Lipoxygenase, Alpha-Toxin) or LH2 (Lipoxygenase homology) domain [24]. This domain binds Ca 2+ ions [25].…”
Section: Resultsmentioning
confidence: 99%